Big data computing - Akerkar, Rajendra (CRC Press, 2014)
"Preface In the international marketplace, businesses, suppliers, and customers do create and consume vast amounts of information. Gartner* predicts that enterprise data in all forms will grow up to 650% over the next five years. According to IDC,